Inhibition of connective tissue growth factor (CTGF/CCN2) in gallbladder cancer cells leads to decreased growth in vitro. Issue 3 (18th April 2013) - Garcia, Patricia; Leal, Pamela; Ili, Carmen; Brebi, Priscilla; Alvarez, Hector; Roa, Juan C.
Summary: Gallbladder cancer (GBC) is an aggressive neoplasm associated with late diagnosis, unsatisfactory treatment and poor prognosis. Previous work showed that connective tissue growth factor (CTGF) expression is increased in this malignancy. This matricellular protein plays an important role in various cellular processes and its involvement in the tumorigenesis of several human cancers has been demonstrated. However, the precise function of CTGF expression in cancer cells is yet to be determined. The aim of this study was to evaluate the CTGF expression in gallbladder cancer cell lines, and its effect on cell viability, colony formation and in vitro cell migration. CTGF expression was evaluated in seven GBC cell lines by Western blot assay. Endogenous CTGF expression was downregulated by lentiviral shRNA directed against CTGF mRNA in G‐415 cells, and the effects on cell viability, anchorage‐independent growth and migration was assessed by comparing them to scrambled vector‐transfected cells. Knockdown of CTGF resulted in significant reduction in cell viability, colony formation and anchorage‐independent growth ( P  <   0.05). An increased p27 expression was observed in G‐415 cells with loss of CTGF function. Our results suggest that high expression of this protein in gallbladder cancer may confer a growth advantage for neoplastic cells.